Forecasting S&P 100 Implied Volatility Using Artificial Neural Network - Roongroje, Thipawan (2009)
Volatility forecast is an important task in financial markets. It has held the most attention among academics and practitioners over the last decades. A good forecast of the volatility of the asset prices over the investment period is a good starting point for assessing investment risk.